Primary renal lymphoma mimicking renal cell carcinoma - Sanju Cyriac; Rajendranath Rejiv; Sundersingh Shirley; Gnana T Sagar (Indian Journal of Urology, 2010)
Primary renal lymphoma is very rare. Lymphomatous involvement of the kidney is often seen as a part of disseminated disease. The prognosis is usually poor with median survival less than a year. It is essential to differentiate between renal cell carcinoma and renal lymphoma in patients presenting with solitary renal masses. We present a 52-year-old lady who presented with a solitary renal mass and was diagnosed to have primary lymphoma of the kidney and discuss briefly about primary renal lymphoma.